Sistem Informasi Manajemen Kearsipan Berbasis Web di Sekretariat DPRD Kabupaten Sumba Barat Daya - Daud Bulu; Yulius Nahak Tetik; Mitra Permata Ayu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The Secretariat of the Regional People's Representative Council (DPRD) of Southwest Sumba Regency plays an important role in supporting local government administration. In carrying out its duties, the Secretariat produces various administrative documents that must be properly managed and maintained. However, archive management is still conducted conventionally through physical storage, which increases the risk of document damage, loss, and inefficiency in retrieval. This study aims to develop a web-based archive management information system to improve the effectiveness of document management. The research methodology involves several systematic stages, including needs analysis, system design, development, and system implementation. Data were collected through observation and interviews to identify existing problems in archive management practices. The results show that the developed system provides significant improvements in managing archives electronically. It enables faster data access, better document organization, and reduced risk of physical damage. Therefore, the system offers a practical solution to enhance administrative efficiency and support digital transformation within the DPRD Secretariat of Southwest Sumba Regency.